2019
DOI: 10.1111/aos.14195
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of trabeculectomy with mitomycin C for glaucomatous eyes with low intraocular pressure on treatment eye drops

Abstract: Purpose: To examine the efficacy and safety of current trabeculectomy with mitomycin C in Japan for glaucomatous eyes with low intraocular pressure (IOP). Methods: Two hundred ninety-four eyes of 294 patients with IOP ≤21 mmHg before surgery were studied; all patients were participants in the Collaborative Bleb-related Infection Incidence and Treatment Study (CBIITS), a multicentre, prospective, cohort study conducted at 34 ophthalmological institutions throughout Japan. All eyes had an intraocular pressure ≤ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Needling procedures were performed at the investigator's discretion, and it is not surprising that all were done in the trabeculectomy group. The needling rate of 20% in the PTVT Study does not seem excessively low and is higher than reported in the TVT Study 2 and large cases series of trabeculectomy with mitomycin C. 3,4 Additional needling procedures may be required during the final 2 years of the PTVT Study to prevent surgical failure. TO THE EDITOR: Failure and success criteria according to intraocular pressure measurements are often used in glaucoma trials 1 to analyze the longevity and comparative success of surgical interventions.…”
Section: Matt Schlenker MD Mscmentioning
confidence: 84%
See 1 more Smart Citation
“…Needling procedures were performed at the investigator's discretion, and it is not surprising that all were done in the trabeculectomy group. The needling rate of 20% in the PTVT Study does not seem excessively low and is higher than reported in the TVT Study 2 and large cases series of trabeculectomy with mitomycin C. 3,4 Additional needling procedures may be required during the final 2 years of the PTVT Study to prevent surgical failure. TO THE EDITOR: Failure and success criteria according to intraocular pressure measurements are often used in glaucoma trials 1 to analyze the longevity and comparative success of surgical interventions.…”
Section: Matt Schlenker MD Mscmentioning
confidence: 84%
“…This is in contrast with a more typical situation where there is a greater effect size as the sensitivity of the outcome increases. 4 Generally speaking, qualified success criteria are harder to interpret owing to the added variable of medication introduction and response. Clinicians could be introducing medications at different IOP levels based on preconceived notions of management for the unmasked intervention, or different interventions may have different IOP responses to medications.…”
mentioning
confidence: 99%
“…An increased risk is observed not only for intraoperative but also postoperative complications related to the filtration bleb, including infectious and metabolite-associated complications, or the development of malignant glaucoma. There is also an elevated risk of hypotony and related complications such as maculopathy, choroidal detachment or the development of cataract in phakic eyes [50]. With drainage implants there is a risk of complications related to the implant itself.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that IOP is not the speci c factor responsible for glaucomatous optic nerve damage, but rather some circulating and metabolic factors. We presume that visual function may be maintained when the IOP is controlled at the target level by surgery or topical medications [30].…”
Section: Visual Acuity and Visual Eld Testmentioning
confidence: 99%